2021
DOI: 10.2147/jaa.s325293
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Pneumorachis – A Case-Based Review

Abstract: Pneumorachis is characterized by the presence of free air in the spinal canal. It is referred by different names in literature such as epidural emphysema, intraspinal air, intraspinal pneumoc(o)ele, spinal epidural and subarachnoid pneumatosis, spinal and epidural emphysema, aerorachia, pneumosaccus, air myelogram, etc. Pneumorachis can be broadly classified as traumatic, iatrogenic, or spontaneous. In this case-based review, we present a case of spontaneous pneumorachis secondary to asthma exacerbation. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 85 publications
1
15
0
Order By: Relevance
“…The incidence of spontaneous PR is currently unknown and believed to be underdiagnosed. A 2021 systemic review that identified 49 cases of spontaneous PR published from 1994 to 2021 supports the rarity of this finding [12]. As a result of its pathophysiology (described below), spontaneous PR is commonly found in combination with air in other cavities, such as subcutaneous emphysema, pneumothorax, and/or pneumomediastinum, as seen in our patient [1].…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…The incidence of spontaneous PR is currently unknown and believed to be underdiagnosed. A 2021 systemic review that identified 49 cases of spontaneous PR published from 1994 to 2021 supports the rarity of this finding [12]. As a result of its pathophysiology (described below), spontaneous PR is commonly found in combination with air in other cavities, such as subcutaneous emphysema, pneumothorax, and/or pneumomediastinum, as seen in our patient [1].…”
Section: Discussionsupporting
confidence: 74%
“…Close monitoring and serial neurologic exams are encouraged to evaluate the progression of neurologic symptoms. Serial spinal imaging and prophylactic antibiotics were generally not advised unless there was concern for cord compression or infection, respectively [1,12]. In the cases reviewed for this report, follow-up imaging generally showed air reabsorbed in the bloodstream in a matter of days to weeks with little to no recurrence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nontraumatic PR usually results from an extension of air from a contiguous site, such as pneumomediastinum, spontaneous pneumothorax, pneumoperitoneum, pneumopericardium, or subcutaneous emphysema. A 2021 case-based review of the literature found six cases of PR triggered by upper respiratory tract infections, five in association with asthma exacerbations, three with vomiting caused by diabetic ketoacidosis, three with emphysematous pyelonephritis, and two with degenerative disc disease [9]. Other cases have also been seen with the Valsalva maneuver, foreign body aspiration, inhalational drug use, and malignancy-related fistulae [5,[7][8][9].…”
Section: Discussionmentioning
confidence: 99%
“…Infectious causes of PR are exceptionally rare but have been reported secondary to epidural abscesses, sacral decubitus ulcers, and intra-abdominal or retroperitoneal infections with gas-forming organisms, including emphysematous infections of the genitourinary tract [7,9]. A handful of cases have been reported of PR secondary to emphysematous pyelonephritis [10][11][12][13], whereas only one other report of PR secondary EC has been reported [14].…”
Section: Discussionmentioning
confidence: 99%